2014
DOI: 10.1016/j.immuni.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Innate Host Defense Requires TFEB-Mediated Transcription of Cytoprotective and Antimicrobial Genes

Abstract: Animal host defense against infection requires the expression of defense genes at the right place and the right time. To understand such tight control of host defense requires the elucidation of the transcription factors involved. Using an unbiased approach in the model Caenorhabditis elegans, we discovered that HLH-30 (known as TFEB in mammals) is a key transcription factor for host defense. HLH-30 was activated shortly after Staphylococcus aureus infection, and drove the expression of close to 80% of the hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
377
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(403 citation statements)
references
References 65 publications
26
377
0
Order By: Relevance
“…In addition, examination of transgenic worms carrying a translational GFP reporter for LGG-1 revealed that the autophagy machinery is targeted to N. parisii cells [42]. (iii) Infection with the extracellular pathogen S. aureus also activates the expression of several autophagy genes and this activation is dependent on the bHLH transcription factor HLH-30, which is required for the expression of 80% of the transcriptional C. elegans response to S. aureus, including AMP genes [23]. Staphylococcus aureus infection-induced autophagosome formation could be observed by analysis of the localization of GFP-tagged LGG-1 in the C. elegans intestine [23].…”
Section: (B) Autophagymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, examination of transgenic worms carrying a translational GFP reporter for LGG-1 revealed that the autophagy machinery is targeted to N. parisii cells [42]. (iii) Infection with the extracellular pathogen S. aureus also activates the expression of several autophagy genes and this activation is dependent on the bHLH transcription factor HLH-30, which is required for the expression of 80% of the transcriptional C. elegans response to S. aureus, including AMP genes [23]. Staphylococcus aureus infection-induced autophagosome formation could be observed by analysis of the localization of GFP-tagged LGG-1 in the C. elegans intestine [23].…”
Section: (B) Autophagymentioning
confidence: 99%
“…(iii) Infection with the extracellular pathogen S. aureus also activates the expression of several autophagy genes and this activation is dependent on the bHLH transcription factor HLH-30, which is required for the expression of 80% of the transcriptional C. elegans response to S. aureus, including AMP genes [23]. Staphylococcus aureus infection-induced autophagosome formation could be observed by analysis of the localization of GFP-tagged LGG-1 in the C. elegans intestine [23]. Worms in which the autophagy genes lgg-1, unc-51 (homologous to human ULK1) and vps-34 (homologous to human phosphoinositide 3-kinaseVPS34) are knocked down by RNAi are more susceptible to S. aureus-mediated killing.…”
Section: (B) Autophagymentioning
confidence: 99%
See 1 more Smart Citation
“…HLH-30/TFEB could also be involved in the regulation of vitellogennins/ lipoproteins modulating lipid homeostasis and ectopic lipid storage under normal and stress-induced conditions. Although HLH-30/TFEB is required under stress conditions to maintain organismal homeostasis and survival (55,80), its function is not restricted to normal conditions. Wild-type nematodes subjected to RNAi against hlh-30 display decreased expression of several autophagy and lysosomal genes.…”
Section: Discussionmentioning
confidence: 99%
“…OPTN expression is known to be regulated by the autophagy regulator transcription factor EB (TFEB) and the inflammatory cytokine TNF-alpha (Nagabhushana et al, 2011;Visvikis et al, 2014). Both autophagic dysfunction and neuroinflammation occur in PD and are linked to pathogenesis (Macchi et al, 2015;Tan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%